REDUPLIKASI KATA BERIMBUHAN BAHASA MELAYU TERNATE - Fachmi Alhadar; Rudi S. Tawari (Kantor Bahasa Provinsi Maluku Utara, 2021)
This article studies the reduplication process of Malay Ternate (BMT). The process of reduplication when compared to Indonesian, has a uniqueness that is not found in Indonesian. By using qualitative methods, this study describes the process of reduplication and its implications for BMT. Reduplication of affixed word in the Malay Ternate can occur multiple times. In the type of verb that forms the verb